Total Knee Arthroplasty in Patients with Dementia - Hernandez, Nicholas M.; Cunningham, Daniel J.; Jiranek, William A.; Bolognesi, Michael P.; Seyler, Thorsten M. (The Journal of Knee Surgery, 2020)
There are few studies evaluating total knee arthroplasty (TKA) in patients with dementia. The purpose of this study was to evaluate the rate of revision, complication, emergency department (ED) visitation, and discharge disposition in patients with dementia undergoing primary TKA. In this retrospective study, we evaluated patients from 2007 to 2017 using a national database. Ninety-day complications in patients with dementia undergoing TKA were increased risk of ED visitation and skilled nursing facility (SNF) disposition (p  ≤  0.05). Two-year complications in patients with dementia undergoing TKA were increased risk of ED visitation and SNF disposition (p  ≤  0.05). Patients with dementia undergoing TKA are at an increased risk of resource utilization.
Keywords: total joint arthroplasty; primary total knee arthroplasty; total knee arthroplasty; dementia; complications